Media networks : architectures, applications, and standards - Moustafa, Hassnaa; Zeadally, Sherali (Boca Raton, Fla. : Taylor & Francis, 2012)
"With a focus on video and audio-visual services, this book considers different media network architectures along with related protocols and standards. It presents different digital TV technologies along with their deployment architectures, discussing promising media content delivery architectures, including Future Internet, Content Delivery Networks, and Content Centric Networks. The author addresses related technical challenges and standardization efforts. Chapters cover the management of media information and immersive technologies that account for advanced services personalization, immersive technologies architectures and applications, e-health, and e-learning"--
pt. 1. Digital TV -- pt. 2. Media content delivery and quality of experience -- pt. 3. User-centricity and immersive technologies.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Multimedia communications; Closed-circuit television; Electronic books